A influência do consumo no design brasileiro do século 19: uma revisão teórica - Toledo, Emmanuel Guedes de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study consists in a literature review on the history of design and focuses on understanding the connections between consumption and practice of design in Brazil in the 19th century. From the textual, thematic and interpretative analysis of a chosen material through a literature review and technical reading, some aspects of consumption and design are identified in Brazil during such period, to then discuss the relevance of consumption for understanding manifestations of design activity in Brazil. The analyzes are based on a literature review that approaches aspects of the articulation between design and consumption as commmodity fetishism, the dynamics of the print market in the industrial era, the establishment of department stores in European urban centers and the manufacturing of articles of luxury in the 18th century. It is observed that some of the main directions of design in its history in the modern world and in Brazil in the nineteenth-century, can be understood through social and cultural aspects revealed from the consumption of industrialized artifacts

O presente estudo consiste em uma revisão teórica na área da história do design e tem como foco a compreensão das conexões entre o consumo e a atividade projetual praticada no Brasil do século 19. A partir da análise textual, temática e interpretativa de um material selecionado por meio de um levantamento bibliográfico e de leitura técnica, são identificados alguns aspectos do consumo e do design no Brasil daquele período, para, em seguida, discutir-se a relevância do consumo para a compreensão de manifestações da atividade projetual em território brasileiro. As análises realizadas baseiam-se numa revisão da literatura que aborda aspectos do consumo articulado ao design, como o fetichismo da mercadoria, a dinâmica do mercado de impressos na era industrial, o estabelecimento de lojas de departamentos em centros urbanos europeus e as manufaturas de artigos de luxo do século 18. Observa-se que alguns dos principais sentidos do design, em sua história no mundo moderno e no Brasil oitocentista, se premitem compreender por meio dos aspectos sociais e culturais revelados a partir do consumo de artefatos industrializados
Keywords: Consumidores; Civilização moderna; Industrialização; Cultura material; Sociedade civil; Consumers